1993
DOI: 10.1002/1097-0142(19931215)72:12<3553::aid-cncr2820721203>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials of agents that reverse multidrug resistance. A literature review

Abstract: Background. The discovery of the P‐170 glycoprotein as a mediator of multidrug resistance (MDR) represents one of the most important research accomplishments in antineoplastic pharmacology during the last decade. Demonstration of P‐170 in epithelial tissues, untreated and chemotherapeutically pretreated human malignancies, and identification of various agents capable of reversing resistance in vitro generated enthusiasm for clinical studies throughout the world. The authors provide an overview of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(105 citation statements)
references
References 40 publications
0
103
0
2
Order By: Relevance
“…The more advanced and pretreated the tumour the greater are the chances it will contain cellular clones with multiple and complex resistance mechanisms. It is therefore not surprising that the results so far with reversing agents in extensively pretreated cancer patients highly resistant to chemotherapy have been disappointing (Rodenburg et al, 1991;Raderer and Scheithauer, 1993;D'Incalci, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The more advanced and pretreated the tumour the greater are the chances it will contain cellular clones with multiple and complex resistance mechanisms. It is therefore not surprising that the results so far with reversing agents in extensively pretreated cancer patients highly resistant to chemotherapy have been disappointing (Rodenburg et al, 1991;Raderer and Scheithauer, 1993;D'Incalci, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…brain [11] and melanoma [12], has sparked interest and elicited a move to understand the multimodal mechanisms of action of this synthetic triphenylethylene [3]. Among the most intriguing properties of tamoxifen, independent of estrogen receptor status, is reversal of multidrug resistance (MDR) [3,13,14]. This has resulted in clinical studies (1/ aimed at exploiting the chemosensitizing properties of tamoxifen [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In small clinical studies of AML and multiple myeloma, promising results have been reported when resistance modifiers have been added to chemotherapy, and trials are under way to investigate whether this can improve treatment results (Sonneveld et al, 1992;List et al, 1993). Clinical studies in solid tumours are, so far, mostly phase I or contain few patients and are therefore not conclusive (Raderer and Scheithauer, 1993).…”
mentioning
confidence: 99%